Innovative Remediation Strategies for Tackling Groundwater Pollution: A Comparative Analysis - Dr. Osama Asanousi Lamma (African Journal of Advanced Pure and Applied Sciences, 2024)
Groundwater pollution poses a pervasive environmental challenge in Alwahat, Libya, necessitating a comprehensive investigation into innovative remediation strategies. This study meticulously examines cutting-edge approaches to groundwater remediation, assessing their comparative efficacy within the unique hydrogeological context of Alwahat. Utilizing a combination of field investigations, water sampling, and laboratory analyses, the research identifies the specific pollutants affecting the groundwater and evaluates the performance of emerging remediation technologies. The comparative analysis encompasses traditional methods alongside advanced strategies such as electrokinetic remediation, phytoremediation, and nanoremediation. Results reveal the nuanced effectiveness of these approaches, considering factors like cost, sustainability, and adaptability to local conditions. Findings from this study contribute valuable insights into tailoring remediation efforts to the specific challenges faced by Alwahat, facilitating informed decision-making for environmental policymakers and practitioners. As the global demand for sustainable water management escalates, this research serves as a crucial reference for mitigating groundwater pollution in arid regions, emphasizing the importance of context-specific innovation in environmental remediation practices.